Implementation of Scientific Approach in English Teaching at SMPN 1 Gringsing Batang - Luluk Fatwiana Muslimah; Ngasbun Egar; Siti Musarokah (ETERNAL (English Teaching Journal), 2017)
This research aimed: 1) to identify the implementation of scientific approach in English teaching at SMP N 1 Gringsing, 2) to identify the problems faced by the teachers and students implementing scientific approach in English teaching, and 3) to know the teachers’ solutions of the problems. The method used in this final project is descriptive qualitative. The writer used observation sheet and documentation gotten by recording the activities, and the lesson plan of the teachers in collecting data. The result of the analysis shows: 1) the implementation of scientific approach in teaching learning process at SMP N 1 Gringsing Batang is running well, although the five steps are not working well because the time was not enough to finish all of steps of scientific approach in one meeting. 2) the problems in teaching learning process were divided into two parts.  The first was problems of the teachers. Here, the first teacher often forgot to give apperception in the opening step as stated in the lesson plan. The teachers found the students were less active in learning process of questioning step. Moreover, the teachers gave same instruction in exploring and associating step by giving same questions but different pattern (written and orally). Then, the teachers were lack in the media of teaching learning process, so it made students bored. The second was problems faced by the students that they were being nervous, afraid, or ashamed if they made a mistake in arranging the question or sentence, and show their work. Sometimes they felt difficult when they found new vocabularies. 3) there were some solutions made by the teachers to solve the problems. They corrected the students’ pronunciation and wrong sentence. The teachers let students to open their dictionary to find the meaning of difficult words. Furthermore, they gave motivation to the students that they should be more active in the teaching and learning process. In addition, the teachers gave punishment by giving questions to students who did not focus in learning process and the students were asked to write what they had learnt on that day in “My Journal”. It was to know the students’ development. Finally, the teachers should improve the techniques in learning process, so the students can receive the material easily.